The influence of social media promotion, word of mouth, and quality service on repurchase intention: The role of trust - Ayu Putri Pertiwi; Risma Putri Nirmala; Riski Saputri; Ipung Totok Andriawan (Sebelas Maret Business Review, 2023)
The coffee business or coffee shop is a sector that is growing rapidly. Coffee shops have evolved into more comfortable and modern places, caused by changes in people's lifestyles and behavior in consuming products and services. This situation also brings tight competition in the coffee shop business, where they must make several efforts to keep their brand selected. Some actions are maximizing social media promotion channels, word of mouth (WOM), and increasing service quality, which are expected to increase trust so that consumer repurchase intention can increase indirectly. This research aims to determine the influence of social media promotion, WOM, and service quality on consumer repurchase intention, both directly and through trust mediation. They are using a population of coffee shop consumers in Surakarta. We take a sample of 200 respondents. This number was obtained from an online survey via the Google Forms platform. The questionnaire results were analyzed using the partial least squares method with the SmartPLS 3.0 software application. The research results reveal that social media promotion, WOM, and quality service directly impact repurchase intention. Meanwhile, indirectly, namely through the mediation of trust, only WOM and quality service significantly affect consumers' intention to repurchase. These results imply that when deciding to repurchase, consumers look at the quality of the product they purchased and pay attention to other things. Therefore, managers or owners need to pay more attention to these details.